Effects of dietary wheat middlings, dried distillers grains with solubles and choice white grease on growth performance, carcass charactersitics, and carcass fat quality of grow-finish pigs - Barnes, Julie A. (Kansas State University, 2011)
Five experiments used 3,004 pigs to determine influences of wheat middlings (Midds), dried distillers grains with solubles (DDGS), and choice white grease (CWG) on growth, carcass traits, and carcass fat quality of finishing pigs and the optimal SID Trp:Lys in growing and finishing pigs fed 30% DDGS. In Exp. 1, pigs fed increasing dietary Midds had decreased (linear; P≤0.02) ADG and G:F. Feeding 30% DDGS did not influence growth performance. For carcass traits, increasing Midds decreased (linear; P<0.01) carcass yield, HCW, and backfat depth (quadratic; P<0.02) but increased (quadratic; P<0.01) FFLI. Feeding 30% DDGS decreased (P<0.03) carcass yield and backfat depth (P<0.01), but increased FFLI (P<0.02) and jowl fat IV (P<0.001). In Exp. 2, feeding 20% dietary Midds decreased (P<0.01) ADG and G:F. Pigs fed diets with increasing CWG had improved ADG (quadratic, P<0.03) and G:F (linear, P<0.01). Dietary Midds or CWG did not affect ADFI. For carcass traits, feeding 20% Midds decreased carcass yield (P<0.05), HCW, backfat depth, and loin depth, while increasing jowl fat IV (P<0.001). Pigs fed CWG also had decreased (linear, P<0.05) FFLI and increased (linear, P<0.01) jowl fat iodine value. In conclusion, feeding Midds reduced pig growth performance, carcass yield, and increased jowl fat IV. In Exp. 3, xylanase supplementation did not improve growth performance or carcass traits of pigs fed different dietary energy and fiber levels. Increasing dietary energy increased (linear; P<0.001) ADG and G:F with no affect on ADFI. Increasing dietary energy increased (linear; P<0.01) yield, HCW, backfat depth, and reduced FFLI (linear; P<0.001) and jowl fat iodine value (linear; P<0.001). Apparent total tract digestibility of ADF improved (P<0.002) with the addition of dietary xylanase; however, there were no differences in any other nutrient digestibility criteria. As dietary energy increased, there was an increase (linear; P<0.02) in apparent digestibility of DM, N, fat, GE, ADF, and NDF. In Exp. 4 and 5, results indicated the optimal SID Trp:Lys was 16.5% from 36.3 to 72.6 kg, but at least 19.5% from 72.6 to 120.2 kg in corn-soybean meal diets containing 30% DDGS.
Keywords: Wheat middlings; DDGS; Finishing pig; Animal Sciences (0475)